Drip pricing and its regulation: Experimental evidence - Alexander Rasch; Miriam Thöne; Tobias Wenzel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2018)
We experimentally examine the effects of drip pricing on seller strategies and buyer behavior as well as the implications for regulation. Sellers set two prices: a base price and a drip price. At first, buyers only observe the base prices and make a tentative purchase decision. Revealing the sellers' drip prices, however, comes at a cost. We find that sellers only compete in base prices and set the highest possible drip price. This makes the base price a reliable indicator for the lowest total price, and few consumers invest in drip-price search. A comparison with Bertrand competition reveals significant effects: With drip pricing, consumer surplus is lower, and seller profits are higher. When there is uncertainty over possible drip sizes, sellers also compete over drips, and consumers more frequently fail to identify the cheapest offer. Bertrand competition also leads to higher consumer surplus and lower firm profits in this case. Hence, our results point to positive effects of drip-price regulation.
Keywords: L13; M3; C9; 330; Drip pricing; Search; Regulation